1990
DOI: 10.1159/000293209
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Pathology in Chronic Pelvic Inflammatory Disease

Abstract: One hundred and sixty-six ovaries of the women of childbearing age suffering from chronic pelvic inflammatory disease (PID) were studied histologically and compared with normal ovaries. The number of mature follicles, cystic atretic follicles, follicular cysts, corpora lutea of menstruation, regressing corpora lutea, and corpus luteum cysts were calculated for each ovary. The main difference between ovaries in chronic PID and normal controls was increase in the number of cystic follicles and follicular and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…**P ≤ 0.05; *P ≤ 0.08 compared with untreated controls; analysis by nonparametric Mann-Whitney U test. ovarian follicle and that patients suffering PID show ovarian pathologies (Bychkov 1990, Pelzer et al 2011, Pelzer et al 2013. The data presented here suggest that GLCs can initiate an innate immune response to pathogen-associated molecules, potentially altering the microenvironment of the follicle.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…**P ≤ 0.05; *P ≤ 0.08 compared with untreated controls; analysis by nonparametric Mann-Whitney U test. ovarian follicle and that patients suffering PID show ovarian pathologies (Bychkov 1990, Pelzer et al 2011, Pelzer et al 2013. The data presented here suggest that GLCs can initiate an innate immune response to pathogen-associated molecules, potentially altering the microenvironment of the follicle.…”
Section: Discussionmentioning
confidence: 74%
“…Although PID is a cause of pelvic pain and infertility, little is known about the effects on the ovary and female gametes. However, it has been shown that patients with PID have reduced follicle numbers and increased cystic follicles and corpora lutea after the resolution of the initial infection (Weiner & Wallach 1974, Bychkov 1990. Retrospective analysis of patients undergoing fertility treatment suggest that increased endometrial LPS reduces IVF success (Kamiyama et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Pelvic inflammatory disease causes pain and infertility, and is the leading cause of gynecological hospitalization of women in the developed world (Ross, 2002). Studies in women suggest that PID causes ovarian changes similar to those seen in the dairy cow following uterine infection (Weiner and Wallach, 1974;Margolis, 1976;Bychkov, 1990). In addition, studies of infection and immunity using primary cells from the bovine uterus and ovary are similar to studies using human endometrial and ovarian cells (Sanchotello et al, 1992;Allhorn et al, 2008;Price et al, 2012).…”
Section: Animal Models Of Uterine Infection and Their Implicationsmentioning
confidence: 99%
“…Its clinical features vary according to the patient's immune and health status. Typically, there are no obvious symptoms and signs of PID until chronic inflammation develops in the pelvic cavity, which can lead to serious consequences, such as preterm labor [2], infertility [3], ectopic pregnancy [4], and pelvic Open Access *Correspondence: akamarucoh1116@gmail.com; d0562@mail.cmuh.org.tw 1 Department of Obstetrics and Gynecology, China Medical University Hospital, Taichung, Taiwan Full list of author information is available at the end of the article organ adhesions [5]. Research has shown that infection and chronic inflammation play an important role in carcinogenesis [6][7][8].…”
Section: Introductionmentioning
confidence: 99%